NOMA as the Cure for Conflict Between Science and Religion: Reply to Ludwik Kowalski's Commentary on the NOMA Principle - Bylica, Piotr (Filozoficzne Aspekty Genezy, 2021)
In my response to Kowalski’s commentary I indicate that: 1) there is an imprecision in Kowalski’s presentation of the NOMA principle; 2) the NOMA principle is not a valid way of presenting theistic religions; 3) the argumentation adopted by Kowalski is inconsistent, due to inconsistency in the NOMA principle itself. The Kowalski’s cure for the “Confrontations Between Theists and Atheists” mentioned in the title of the Kowalski’s commentary is the postulate of a “miracle-free” theism, which means the elimination of theism. Another important weakness of Kowalski’s proposal and of the application of the NOMA principle in general is the self-contradictoriness of this position: when we decide on the truth value of this or that factual religious statement by reference to science, then we deny the essence of the NOMA principle itself.